Efek Penghambatan Gingerol Terhadap 8- Hidroksideoksiguanosin (8-OHdG) Penginduksi Sel Kanker, HepG2 - Harliansyah, Harliansyah (Lembaga Penelitian Universitas YARSI, 2011)
Oxidative stress can damage the function of normal cells and cause pathological conditions. One of the products of oxidative stress is the formation of compounds 8-hydroxy-2'deoksiguanosine (8-OHdG), which is the result of oxidation of the structure of DNA and a risk factor for cancer, atherosclerosis and diabetes on the body's tissues. In this research note that the administration of 1000 ug / ml gingerol reduces the formation of 8-OHdG hepatoma cells (HepG2) is 81.62 Ã‚Â± 5.59 ng / ml versus control significantly (p 0.05; r = 0.76). This result ensures that the antioxidant properties contained in the gingerol can inhibit the activity of free radical markers (8-OHdG) so likely as a preventative against degenerative diseases such as cancer cells.